The duodenal mucosa associated microbiome, visceral sensory function, immune activation and psychological comorbidities in functional gastrointestinal disorders with and without self-reported non-celiac wheat sensitivity - Ayesha Shah; Seungha Kang; Nicholas J Talley; Anh Do; Marjorie M Walker; Erin R Shanahan; Natasha A Koloski; Michael P Jones; Simon Keely; Mark Morrison; Gerald J Holtmann (Gut Microbes)
Frequently, patients with functional gastrointestinal disorders (FGIDs) report intolerance of wheat products. We compared gastrointestinal symptoms, sensory function, psychiatric comorbidities, gut-homing immune cells, and duodenal mucosa-associated microbiome (d-MAM) in FGID patients and controls with and without self-reported wheat sensitivity (SR-NCWS). We recruited 40 FGID patients and 20 controls referred by GPs for treatment. Gastrointestinal/extraintestinal symptoms, visceral sensory function, psychological comorbidities, and SR-NCWS were assessed in a standardized approach. Peripheral gut homing T-cells (CD4+α4+β7+CCR9+/CD8+α4+β7+CCR9+) were quantified, and the d-MAM was assessed by DNA sequencing for 46 subjects. Factors of bacterial genera were extracted utilizing factor analysis with varimax rotation and factors univariately associated with FGID or SR-NCWS included in a subsequent multivariate analysis of variance to identify statistically independent discriminators. Anxiety scores (p < .05) and increased symptom responses to a nutrient challenge (p < .05) were univariately associated with FGID. Gut homing T-cells were increased in FGID patients with SR-NCWS compared to other groups (p all <0.05). MANOVA revealed that anxiety (p = .03), visceral sensory function (p = 0.007), and a d-MAM factor comprise members of the Alloprevotella, Prevotella, Peptostreptococcus, Leptotrichia, and Veillonella lineages were significantly (p = .001) associated with FGID, while gut homing CD4+α4+ β7+CCR9+ T-cells were associated (p = .002) with SR-NCWS. Compared to controls, patients with and without SR-NCWS show that there are shifts in the amplicon sequence variants within specific bacterial genera between the FGID subgroups (particularly Prevotella and Streptococcus) as well as distinct bacterial taxa discriminatory for the two different FGID subtypes. Compared to controls, both FGID patients with and without SR-NCWS have an increased symptom response to a standardized nutrient challenge and increased anxiety scores. The FGID patients with SR-NCWS – as compared to FGID without SR-NCWS (and controls without SR-NCWS) – have increased gut homing T-cells. The d-MAM profiles suggest species and strain-based variations between the two FGID subtypes and in comparison to controls.